2015
DOI: 10.1021/acs.biomac.5b00226
|View full text |Cite
|
Sign up to set email alerts
|

More Than Just Fibers: An Aqueous Method for the Production of Innovative Recombinant Spider Silk Protein Materials

Abstract: Spider silk is a striking and robust natural material that has an unrivaled combination of strength and elasticity. There are two major problems in creating materials from recombinant spider silk proteins (rSSps): expressing sufficient quantities of the large, highly repetitive proteins and solvating the naturally self-assembling proteins once produced. To address the second problem, we have developed a method to rapidly dissolve rSSps in water in lieu of traditional organic solvents and accomplish nearly 100%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 38 publications
3
77
0
Order By: Relevance
“…Most studies characterizing post-spin stretching of silk-based fibers have reported carrying out this step manually with the use of forceps or tweezers 9,11,12,42 , with some reports of using controlled post-spin stretching apparatuses (e.g. 16,44 ). An apparatus can certainly be envisioned that incorporates the post-spin stretching as part of an automated fiber production process 16,44 .…”
Section: Post-spin Stretching Of As W 3 Fibersmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies characterizing post-spin stretching of silk-based fibers have reported carrying out this step manually with the use of forceps or tweezers 9,11,12,42 , with some reports of using controlled post-spin stretching apparatuses (e.g. 16,44 ). An apparatus can certainly be envisioned that incorporates the post-spin stretching as part of an automated fiber production process 16,44 .…”
Section: Post-spin Stretching Of As W 3 Fibersmentioning
confidence: 99%
“…16,44 ). An apparatus can certainly be envisioned that incorporates the post-spin stretching as part of an automated fiber production process 16,44 . However, this requires knowledge of the optimal degree of post-spin stretching.…”
Section: Post-spin Stretching Of As W 3 Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…While these production systems can produce soluble forms of the rSSPs, high level expression can induce precipitation as well, as during the purification process, as the rSSPs becomes less dilute and more pure, the rSSPs both spontaneously self-assemble and precipitate or, are salted out of solution as part of that process [25,29,30]. The purified rSSPs can be lyophilized for storage, generally further reducing the aqueous solubility [29,31]. Necessary to forming fibers, and other materials, is that the rSSPs must be dissolved.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of the web and energy required to rebuild it would be an evolutionary disadvantage. As such, when rSSPs are produced from these same sequences and precipitated, β-sheets form much like in the fiber and the rSSPs are largely water insoluble [31]. Due to this solubility issue, the majority of rSSPs have been solubilized using 1,1,1,3,3,3 Hexafluoroisopropanol (HFIP) [25,26,27,28,29,32,33].…”
Section: Introductionmentioning
confidence: 99%